How to Construct a Societal-Political Reality? (On the Philosophical Underpinnings of the Article “Political Strands in Ancient Armenia” by N. Adonts) - Mkrtchyan, Naira (Bulletin of Yerevan University E: Philosophy, Psychology, 2017)
At the end of the 19th and in the first half of the 20th centuries Armenian social thinkers and historians faced the issues of dealing with the past and with the tradition of past historiography aiming to solve the problems of modernization of Armenian society and its transition to modernity. In this respect and at first glance N. Adonc reveals a paradoxical approach: to rely upon the old historiography and at the same time to break with its tradition. In the proper cognitive position provided by the frame of modernity he constructs a societal-political reality of Armenians in the context of transition from premodernity into modernity. Here, the central role is played by the contradiction between the two political streams which have existed throughout centuries and ahave been embodied in aristocracy. In this way N. Adonc proposes his own unique approach to these issues in comparison to other existing approaches.
Keywords: societal-political reality, construction, proper cognitive position, political streams, contradiction, “great political question”